Keep my share of rice in the cupboard: ethnographic reflections on practices of gender and agency among Dalit women in the Central Himalayas - Polit, Karin M. (2006)
The book illuminates various performative practices in Judith Butler's sense which construct gender as integral parts of everyday and ritual practices and are a constitutional of people’s gendered habitus. It describes in detail how low-caste (Mistari, Lohari and Tamta) women in Garhwal, Uttarakhand, India are able to exercise agency while being restricted and restrained by a complicated net of power-relations. Based on extensive ethnographic research in the villages of Chamoli, a high altitude district in the Central Himalayas of North India, the author examines women’s songs, ordinary conversations, my ethnographic observations and especially the stories women told me about themselves, in order to understand what shapes their lives and how female agency – that is, their ability to shape their lives – is constituted and restricted through habitus, gender performativity, and performances of gender.
Online publiziert: 2010
Keywords: Hochschulschrift; Rituelle Magie; Ritual; Dalit; Geschlechterforschung; Butler, Judith / Gender trouble; Garhwal; Uttarākhaṇḍa